By-Product from Pyrolysis of Tar-Sand in Blend with Gray-King Assessed Nigerian Coals for Coke Production - Ryemshak, S. A; Jauro, A; Chindo, I. Y; Ekanem, E. O; Ayeni, F. A (International Journal of Chemistry and Materials Research, 2015)
Thermochemical decomposition of Ondo tar-sand was carried out at a temperature of between 190–250°C in a constructed metal retort, and a yield of 66.66 % bitumen was obtained. Some important parameters of coal for blend simulation, such as the rheological and agglomerating properties of coal samples from – Garin Maiganga (GMG), Chikila (CHK), Lamza (LMZ), Shankodi-Jangwa (SKJ), Afuzie (AFZ) were determined by Gray-King assay test to assess their suitability for blending in coke making. The results showed that all the coals had poor thermoplastic properties that cannot agglomerate on heating because of their low level of fluidity, even though SKJ had an appreciable coke yield of 82.60 % with coke type C indicating that it was weakly coking. Thereafter, formulation of binary blend of coal-bitumen by weight (10 % bitumen and 90 % pre-heated coal samples at about 150 oC) was carried out. And the feasibility of the blend for industrial coke production was investigated by physico-chemical analysis, which revealed that the coking properties of the blend had been improved: Gieseler fluidity/plastic property in dial division per minute (DDPM) for LMZ = 76; CHK = 15; AFZ = 37; GMG = 18 and SKJ = 390, which might produce metallurgical coke with good chemical and mechanical properties.